Community, solidarity, and belonging : levels of community and their normative significance - Mason, Andrew, 1959- (Cambridge University Press, 2000)
Communities can be of different kinds, and exist at different levels in society. This book systematically explores the relationship between the state, and communities existing at local, national and global levels. It will be of interest to students of political theory, philosophy and international relations.